PENGARUH KEPEKATAN NUTRISI DAN BERBAGAI MEDIA TANAM PADA PERTUMBUHAN SERTA PRODUKSI BAWANG MERAH (Allium ascalonicum L) DENGAN HIDROPONIK NFT - Shamora Della Hoya Simbolon; Ernita; M.Nur (DINAMIKA PERTANIAN, 2018)
ABSTRACT The purpose of this study was to investigate the interaction of the application of AB Mix nutrition and growing media on the growth and production of Shallots (Allium ascalonicum L.) on NFT hydroponics. This study uses a ]Compound Plot Design in the form of a Completely Randomized Design consisting of the main plot, namely the nutrient concentration of AB Mix (N) and subplots of planting media (M). Nutrition AB Mix consists of 4 treatment levels, 600, 1200, 1800, 2400 ppm / l water and various planting media treatments consisting of 3 levels, namely husk, cocopeat, and sawdust charcoal media. Each experimental unit consisted of 4 plants and 2 plants used as samples. The parameters observed were as follows: plant height, harvest age, number of tubers, wet tuber weight, dry tuber weight, tuber weight per tuber, tuber weight loss. The observations of each treatment were statistically analyzed and continued with further tests of Honest Significant Difference at the 5% level. The interaction of the application of AB Mix nutrition and planting media had a real effect on all parameters, with the best AB Mix 1800 ppm and cocopeat growing media. The effect of AB Mix main plot has significantly affected all parameters observed with the best treatment of AB Mix 1800 ppm nutrition. The effect of subplot planting media significantly affected all parameters of observation with the best treatment of cocopeat growing media Keywords: AB Mix, Shallots, NFT hydroponics